Reliability and contributing factors to a newly developed reactive agility test performance - Horníková, H.; Skala, F. (Journal of Human Sport & Exercise, 2025)
This study assessed the intra-session reliability and the impact of cognitive and physical factors on the performance of a newly developed Triple Y reactive agility test (3YRAT). Twenty-eight male soccer players (12.74 ± 0.93 years, 161.14 ± 13.46 cm, 49.81 ± 9.73 kg) completed the 3YRAT, visual inhibition task (Go/No-go), choice reaction test, and 10 m sprint test. The 3YRAT demonstrated good reliability (ICC = 0.85 with 95 % CI = 0.71-0.93; CV = 2.3 %; SEM = 0.31s; MDC = 0.85s). The time in 3YRAT was significantly correlated with 10 m sprint time (r = 0.74, p < .001), and the response times in cognitive tests (Go/No-go: r = 0.48, p = .01; choice reaction: r = 0.41, p = .03). Regression analysis found that acceleration sprint speed decision-making, and visual inhibition were the significant predictors of 3YRAT performance, explaining 70 % of the variance (R2 = .70). Overall, both motor (38 %) and cognitive components (32 %) significantly contributed to the 3YRAT performance. This study introduced a new and reliable procedure for assessing reactive agility in youth soccer players, which could be applicable to other athletes of "agility-saturated" sports. This test represents a compromise between force- and velocity-oriented changes of direction, balancing the demands on perceptual-cognitive skills and motor abilities in reactive agility tasks.